2013
DOI: 10.1111/jocn.12071
|View full text |Cite
|
Sign up to set email alerts
|

Finding meaning despite anxiety over life and death in amyotrophic lateral sclerosis patients

Abstract: The balance between anxiety over life and death and finding meaning in life indicates the importance of support through the whole disease process. Both disease-specific problems and existential questions must be tackled. Nurses and other professionals need to be aware of the patients' existential qualms. There is a need to focus on what is important for the individual, and emphasis must be placed on where that person can find meaning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 30 publications
4
74
0
1
Order By: Relevance
“…It would probably help them in coping with the situation and find meaning in life if they could talk about those kinds of feelings and obtain answers about possible misunderstandings both during the disease process and after the partner had passed away. As shown in this and other studies (see Olsson Ozanne et al, 2012;Ozanne et al, 2013), spouses and partners could find it difficult to talk with each other about their feelings and thoughts. Hence, although it might be preferable to provide individual support for spouses, it is also necessary to give spouses and patients joint support and help each to see the other's situation so that they can be there for each other.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…It would probably help them in coping with the situation and find meaning in life if they could talk about those kinds of feelings and obtain answers about possible misunderstandings both during the disease process and after the partner had passed away. As shown in this and other studies (see Olsson Ozanne et al, 2012;Ozanne et al, 2013), spouses and partners could find it difficult to talk with each other about their feelings and thoughts. Hence, although it might be preferable to provide individual support for spouses, it is also necessary to give spouses and patients joint support and help each to see the other's situation so that they can be there for each other.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have examined manageability among the spouse-patient pairs and finding meaning among patients (Olsson Ozanne et al, 2012;Ozanne et al, 2013). Our study was performed to reveal experiences of finding meaning among spouses of people living with ALS.…”
Section: Designmentioning
confidence: 97%
“…Emotional coping techniques may be particularly beneficial during the initial stages of adjusting to the onset of severe disability (Lule, et al, 2009) when people typically deal with significant anxiety, denial, depression, and internalized anger (Glover-Graf, Millington, & Marini, 2012). People with SSPI may also chronically suffer from anxiety (Grossman, et al, 2010; Ozanne, Graneheim, & Strang, 2013), depression (Grossman, et al, 2010), fatigue (Grossman, et al, 2010), and pain (Hirsh, Kratz, Engel, & Jensen, 2011; Vogtle, Malone, & Azuero, 2013). These are all areas that are known to be improved by MM in non-SSPI populations, as was cited in the previous paragraph.…”
Section: Introductionmentioning
confidence: 99%
“…Montel et al 35 found that anxiety and somatic disorders increased over time in their ALS population; the authors suspected both physical deterioration and fear of death as factors that exacerbated or caused anxiety in the patients they studied. Ozanne et al 36 noted that anxiety in their (ALS) population was related to fear of dying in distress (choking to death or gasping for breath). As with depression, anxiety is often a treatable illness.…”
Section: Symptom Management: Depression/anxietymentioning
confidence: 99%